Photon generation in ferromagnetic point contacts - Kadigrobov, A.M.; Shekhter, R.I.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We show theoretically that a significant spin accumulation can occur in electric point contacts between two ferromagnetic electrodes with different magnetizations. Under appropriate conditions an inverse population of spin-split electronic levels results in stimulated emission of photons in the presence of a resonant electromagnetic field. The intensity of the emitted radiation can be several orders of magnitude higher than in typical semiconductor laser materials for two reasons. (1) The density of conduction electrons in a metal point conduct is much larger than in semiconductors. (2) The strength of the coupling between the electron spins and the electromagnetic field that is responsible for the radiative spin-flip transitions is set by the magnetic exchange energy and can therefore be very large as suggested by Kadigrobov et al. [Europhys. Lett. 67, 948 (2004)].